THE PHYSICAL LABORATORY ACTIVITIES WITH PROBLEM SOLVING APPROACH TO INCREASE CRITICAL THINKING SKILL AND UNDERSTANDING STUDENT CONCEPT - Eli Trisnowati; Firdaus Firdaus (JURNAL PENA SAINS, 2017)
This study aims to investigate the description of the improvement of students’ critical thinking skills and the concept understanding by implementing the problem-solving approach. This study was in laboratory activities. This study was done in four times meeting. The try out subjects was 31 students of grades X of MAN Yogyakarta III. This research is using the quasi experimental method with the pretest-posttest design. The data were collected by using multiple choices tests with assessment rubric and observation sheets. The data are analyzed by using multivariate analysis. Based on the result, the gain standard value of students’ conceptual understanding and students’ critical thinking skills for grade X who learned through student’s worksheet with a problem-solving approach, called treatment class, are higher than students who learned without student’s worksheet with a problem-solving approach, called control class.  Keywords: concept understanding, critical thinking skills, laboratory activities, problem-solving approach. Kata Kunci: kegiatan laboratorium, keterampilan berpikir kritis, pemahaman konsep, pendekatan problem solving.